Service Quality at Sekolah Citra Berkat Surabaya and Its Impact on Parents’ Intention to Continue Their Children’s Next Education - Ongkowidjojo, Anneke; Teofilus (Faculty of Psychology, Universitas Medan Area, 2025)
The primary aim of this research study is to investigate service quality's influence on parents' intention to continue their child's education at Sekolah Citra Berkat Surabaya, which is a private K–12 school associated with the Ciputra Education Foundation. The study explored five important service quality dimensions through the SERVQUAL model of Parasuraman, Zeithaml, and Berry (1988), which included: physical dimensions, policy, personal interaction, problem solving and reliability. The study got 191 parents’ responses who completed self-reported surveys, which were explored using Confirmatory Factor Analysis (CFA) by the researchers to measure validity and reliability. The findings provided evidence that all constructs had high internal reliability as the Cronbach’s alpha coefficients varied from 0.878 and 0.949. The model explained 71% of the variance in the parents' willingness to continue their child's education. The results within the model identified reliability, problem solving, and transparency of policy as the main service quality dimensions of the parents' willingness to continue their child’s education; physical dimensions and personal interaction were reported as less significant. Accordingly, reliable service, effective problem solving, and transparent policy are essential service quality dimensions to retain any parental commitment. The study also extends the SERVQUAL model for use in K–12 education within the context of Indonesia and presents insights for educational managers who are concerned with parental retention.